PENGARUH KUALITAS PELAYANAN, STORE ATMOSPHERE, DAN HARGA TERHADAP KEPUASAN KONSUMEN MIE BANGKA 25 SURAKARTA - Rachel Lita Daniati; Marjam Desma Rahadhini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
Customer satisfaction is an important factor in the sustainability of culinary businesses operating in highly competitive markets. Kedai Mie Bangka 25 Penumping Surakarta is one of the culinary businesses in Surakarta City that offers a distinctive attraction through its modern Chinese cultural interior design, featuring red color elements, oriental decorations, and Bangka–Tionghoa murals that create an aesthetic and Instagramable atmosphere. This study aims to analyze the factors influencing customer satisfaction, including service quality, store atmosphere, and price, among consumers of Mie Bangka 25 Penumping Surakarta. The population of this study consists of consumers who made purchases at Kedai Mie Bangka 25 Penumping Surakarta. The sample size was 100 respondents, determined using the Leedy technique. The sampling method used was non-probability sampling, with data collected through questionnaires. The data analysis techniques employed include validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination test. The results indicate that all questionnaire items are valid and reliable, and the classical assumption tests—including multicollinearity, autocorrelation, heteroscedasticity, and normality tests—were successfully met. The multiple linear regression analysis shows that all regression coefficients have positive values, with the regression equation: Y = 3.961 + 0.313 X1 + 0.582 X2 + 0.085 X3 indicating that service quality (X1), store atmosphere (X2), and price (X3) influence customer satisfaction at Mie Bangka 25 Penumping Surakarta. The hypothesis testing results reveal that service quality and store atmosphere have a significant effect on customer satisfaction, while price does not have a significant effect on customer satisfaction at Mie Bangka 25 Penumping Surakarta. The F-test indicates that the research model is appropriate. The coefficient of determination shows that service quality, store atmosphere, and price explain 58.4% of customer satisfaction.